2009
DOI: 10.1111/j.1464-410x.2008.08117.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life 3 years after high‐dose intensity‐modulated radiotherapy with gold fiducial marker‐based position verification

Abstract: OBJECTIVE To evaluate the change in quality of life (QoL) 3 years after high‐dose intensity‐modulated radiotherapy (IMRT) using gold fiducial marker‐based position verification in patients with locally advanced prostate cancer. PATIENTS AND METHODS Between October 2003 and November 2004, 95 patients with locally advanced prostate cancer were treated with 76 Gy IMRT with gold‐fiducial marker‐based position verification. Before treatment (baseline) and 1, 6 and 36 months after RT the QoL was measured using the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
6
22
3
Order By: Relevance
“…Longitudinal studies on QoL in patients with CRT for prostate cancer are rare [2,14,16,18,19,27,30], and mostly have a follow-up of ≤ 1 year [2,14,16,18,27,30]. In concordance with our results, these studies demonstrate that QoL is not profoundly impaired by CRT and that there is only a temporary deterioration of a limited number of QoL domains during or shortly after therapy [14,18,27] [14].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Longitudinal studies on QoL in patients with CRT for prostate cancer are rare [2,14,16,18,19,27,30], and mostly have a follow-up of ≤ 1 year [2,14,16,18,27,30]. In concordance with our results, these studies demonstrate that QoL is not profoundly impaired by CRT and that there is only a temporary deterioration of a limited number of QoL domains during or shortly after therapy [14,18,27] [14].…”
Section: Discussionsupporting
confidence: 87%
“…In both groups, a temporary deterioration in physical role restriction and an improvement in emotional role restriction occurred. A recent publication of this study group disclosed a significant improvement of emotional role restriction and functioning, change in health, mental health, and insomnia 3 years after IMRT with 76 Gy for 95 patients as compared with baseline levels before treatment [19]. Sexual activity was significantly decreased at 3 years.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…16,17,29,30 Zelefsky et al compared the toxicity and outcomes of high-dose (86.4 Gy) radiotherapy delivered by IGRT with GM implantation versus non-IGRT. 17 The incidence of grade !2 GU toxicity was significantly lower in the IGRT group than in the non-IGRT group (10.4% vs 20%), and multivariate analysis showed that IGRT was associated with a decreased incidence of late GU toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that-independently of the used generic score-global HRQOL is mostly not significantly or relevantly affected by radiotherapy side effects also was reported by the majority of recent published prospective and/or longitudinal studies using 3D-CRT, IMRT, or brachytherapy (BT) alone or in combination with EBRT (Geinitz et al 2010;Goineau et al 2013;Huang et al 2010;Lips et al 2009;Pardo et al 2010;Roeloffzen et al 2010;Schaake et al 2013), even after dose escalation (Goineau et al 2013;Lips et al 2009;Marchand et al 2010), when comparing baseline global HRQOL scales with the changes during follow-up. Though some studies have the limitation of a short follow, there is a growing number of long-term studies.…”
Section: 1mentioning
confidence: 63%